Interference suppression through power allocation for massive MIMO systems with channel aging - Shubhi, I.; Pamungkasari, P.; Juwono, Filbert Hilman; Dharmanto, S. (2018)
© 2017 IEEE. To acquire an optimum potential of massive multiple-input multiple-output (MIMO), congruity between pre-coder and the actual channel is required. This circumstance, however, is hard to obtain when the mobile station (MS) is moving in a multipath environment and experiencing channel aging. Suffering channel aging, a mismatch between the precoder matrix and the actual channel matrix occurs which causes interuser interference at the MS. To tackle this problem, we propose a channel prediction based power allocation technique for time-varying massive MIMO. First, we estimate Doppler shift experienced by the BS to create a channel prediction. Afterward, we conduct recursive power allocation with the goal of minimizing channel aging effect at the MS. Using the proposed technique, each MS only suffers a certain interference level which still can be handled by the MS. Through computer simulation, it is shown that our proposed technique enables the time-varying massive MIMO transmission without a significant addition to computational complexity.